The Effect of Using Interactive Digital Storytelling Media on Students’ Narrative Writing Skills and Cognitive Load - Zuhad; Muhammad Rinov Cuhanazriansyah; Salsabilla Zetia Ramadhani; Permata Ayu Rahmawati (Universitas Putra Indonesia YPTK Padang, 2026)
Narrative writing requires high-order cognitive processing, yet conventional static instruction frequently fails to provide adequate cognitive scaffolding, resulting in student writer's block and cognitive overload. This study investigates the impact of an Interactive Digital Storytelling (IDS) platform on secondary students' narrative writing performance and cognitive load allocation using a quantitative true experimental pretest-posttest control group design (). Participants were randomly assigned to an experimental cohort utilising IDS or a control cohort receiving conventional text-based instruction. Outcomes were evaluated via analytic writing rubrics, a tri-dimensional cognitive load scale, and multivariate analysis of variance. Results revealed a statistically significant overall treatment effect for IDS (). The experimental group achieved significantly higher posttest writing scores () than the control group (), demonstrating marked improvements in plot organisation and lexical diversity. Crucially, while intrinsic cognitive load remained equivalent between groups, the IDS platform significantly reduced extraneous cognitive load ( vs ) and increased germane cognitive load ( vs ). In conclusion, ergonomically designed interactive media act as cognitive amplifiers by streamlining interface mechanics and optimizing human working memory for creative schema construction in language pedagogy.